I, michael bennett ebook - Patterson, James (Michael Bennett, 2012)
Police officers shot . . . judges murdered . . . and Detective Michael Bennett is the killer's next target. Detective Michael Bennett arrests an infamous Mexican crime lord in a deadly chase that leaves Bennett's lifelong friend dead. From jail, the prisoner vows to rain epic violence down upon New York City-and to get revenge on Michael Bennett. To escape the chaos, Bennett takes his ten kids and their beautiful nanny, Mary Catherine, on a much-needed vacation to his family's cabin near Newburgh, New York. But instead of the calm and happy town he remembers from growing up, they step into a nightmare worse than they could have ever imagined. Newburgh is an inferno of warring gangs, and there's little the police-or Bennett-can do to keep the children safe. As violence overwhelms the state, Bennett is torn between protecting his hometown and saving New York City. A partner in his investigations, federal prosecutor Tara McLellan, brings him new weapons for the battle-and an attraction that endangers his relationship with Mary Catherine. A no-holds-barred, pedal-to-the-floor, action-packed novel, I, Michael Bennett is James Patterson at his most personal and most thrilling best.